Características sociodemográficas y clínicas de pacientes a los que se les realizaron exodoncias de dientes permanentes en la clínica de adultos UAN sede Armenia 2015 - 2019 - Herrera Parra, Carol Tatiana; Hernández Aguirre, Nikolay Steven; García García, Aura Cristina (Universidad Antonio Nariño, 2021)
The aim of this work was to characterize clinically and sociodemographically the patients treated with exodontia treatment at the Antonio Nariño university in Armenia, in the 2015 – 2019 period